Out of the silent planet - Lewis, C. S (Scribner Paperback Fiction, 1965)
Christian fiction, fantasy and C.S. Lewis but I found "Out of the Silent Plant" hard to get through. Maybe I expected too much given C.S Lewis' powerful "Mere Christianity." The look is loaded with wisdom but not enough to prompt me to recommend the book.